2021
DOI: 10.1038/s41598-021-91364-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and safety of various management options for large upper ureteric stones a systematic review and network meta-analysis

Abstract: To compare the safety and efficacy of various surgical modalities to manage large (> 1 cm) upper ureter stones. Systematic literature search was conducted to include all randomized studies comparing various treatment options for large (> 1 cm) upper ureteric stones. This review included 13 randomized studies with 1871 patients. Laparoscopic ureterolithotomy (LUL) and percutaneous nephrolithotomy (PNL) were superior to ureteroscopy (URS) and shockwave lithotripsy (SWL) for stone-free rates and need for au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…This conclusion is essentially the same as in the meta-analysis by Sharma et al on adult kidney stones. However, these two studies included fewer RCTs, and their findings need more high-quality RCTs for validation ( 35 , 36 ). In the study by Gu et al, in contrast to micro-PCNL, RIRS had a higher SFR and more hemoglobin loss, and no differences were identified in hospitalization, fluoroscopy durations, or complication rates ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is essentially the same as in the meta-analysis by Sharma et al on adult kidney stones. However, these two studies included fewer RCTs, and their findings need more high-quality RCTs for validation ( 35 , 36 ). In the study by Gu et al, in contrast to micro-PCNL, RIRS had a higher SFR and more hemoglobin loss, and no differences were identified in hospitalization, fluoroscopy durations, or complication rates ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that this study was plagued by the poor quality of included studies. Thus the choice of a treatment modality in a given situation will continue to depend upon patient-and surgeon-driven factors until a good-quality randomized controlled study comparing all the four surgical procedures for large upper ureteric stones comes up [26]. Another meta-analysis study was performed to investigate the safety and efficacy of minimally invasive surgical ureterolithotomy in comparision with URL for the treatment of large ureteric stones.…”
Section: Discussionmentioning
confidence: 99%
“…По тяжести осложнений (Clavien -Dindo ≥ III, в смысловом восприятии от лучшего к худшему): литотомия > ударно-волновая литотрипсия > уретероскопия > PNUL [5]. Аналогичные результаты получены и в ряде других работ, где большинство авторов отмечают высочайший рейтинг свободы от камней после уретеролитотомии, равный или близкий 100 % [8][9][10][11]. Подобные выводы сделаны при сравнении нефролапаксии с лапароскопической пиелолитотомией [12].…”
Section: рис 1 Roc-кривая для многофакторной логит-регрессии предикто...unclassified